Prognostic Significance of Substance P/Neurokinin 1 Receptor and Its Association with Hormonal Receptors in Breast Carcinoma. (13th October 2021) - Mehboob, Riffat; Gilani, Syed Amir; Hassan, Amber; Sadaf; Tanvir, Imrana; Javaid, Shaista; Khalid, Sidra; Hasan, Sana; Waseem, Humaira; Alwazzan, Ahmad; Munoz, Miguel
Abstract : Expression and immunolocalization of Substance P (SP)/Neurokinin-1 Receptor (NK-1R) in breast carcinoma (BC) patients and its association with routine proliferative markers (ER, PR, HER2/neu, and Ki-67) were evaluated. A cross-sectional study was performed on 34 cases of BC. There were 23 cases of group A (grade III), 8 of group B (grade II), and only 3 cases of group C (grade I). All samples were then processed for SP and NK-1R immunohistochemistry for few cases. 14/23 cases (61%) of group A, 7/8 cases (88%) of group B, and 2/3 (67%) cases of group C were SP positive. Overall, strong staining (≥10% tumor cells), labeled as "+3, " was observed in 9/14 (64.2%) cases of group A and 1/8 (12.5%) cases of group B. Moderate staining labelled as "+2" (in ≥10% tumor cells) was observed in 3/14 (21.4%) cases of group A and 4/8 (50%) cases of group B. Weak positive staining "+1" was observed in only 2/14 (14.28%) cases of group A, 2/8 (25%) cases of group B, and all 2/2 (100%) cases of group C. SP and NK-1R are overexpressed in breast carcinomas, and there is significant association between the grade of tumor and their overexpression.